A escrita como resistência contra o apagamento literário e social nos contos de Conceição Evaristo e Dina Salústio - Santana, Maria Karolyne Reis (2024)
Studying literature also leads us to reflect on it as a timeless phenomenon that is always evolving, for this reason there are books that even though they are part of the literary canon, at some point according to social changes they are excluded and silenced from these places, as is the case of books written by black people. The aim of this paper is to demonstrate, through the short stories of Conceição Evaristo and Dina Salústio, how they, as black women, reaffirm their existence within the social and literary environment. Investigating how their works contribute to plural narratives allows us to consider their writings as a means of making historically marginalized subjects more accessible and contributes to the study of anti-racist and decolonial literatures. Researching these literatures offers another dimension in understanding their significance for studying the histories of African peoples and those of the diaspora, narrating experiences and issues that are part of the contemporary social context. The methodology used is based on the selective reading of theoretical texts such as Memórias da Plantação - episódios de racismo cotidiano (2019) by Grada Kilomba, Discurso Sobre o Colonialismo (1978) by Aimé Césaire, and Dispositivo de Racialidade (2023) by Sueli Carneiro, among others. These texts provide the theoretical foundation for this research to understand exclusion, structural racism, violence, and silencing, which are studied along with the analysis of selected short stories from the works: Olhos d'água (2020) and Insubmissas Lágrimas de Mulheres (2016) by Conceição Evaristo, and Mornas Eram as Noites (2002) and Filhos de Deus (2018) by Dina Salústio. This bibliographical research was carried out by systematically reading scientific texts and works published in virtual and conventional media, as well as observing everyday life. Thus, the research is qualitative, as it is understood that qualitative research is relevant for constructing data and answers to real and social problems.